Effect of gelatinization and swelling degree on the lubrication behavior of starch suspensions. (1st September 2022) - Ji, Lei; Zhang, He; Cornacchia, Leonardo; Sala, Guido; Scholten, Elke
Abstract: This research aimed to investigate the effect of starch gelatinization and swelling degree on the lubrication properties of starch aqueous suspensions. Three types of maize starch with different amylose content of 70% (HAS), 25% (NS), and <1% (WS) were used to vary the swelling capacities. The granule suspension of NS showed the highest swelling factor (SF) of 26.5, and gave the best lubrication capacity by decreasing friction by 78%. WS was only able to decrease friction by 50% due to a lower swelling capacity. The leached-out amylose increased friction of highly swollen granules (SF = 26.5) but decreased friction of stiff granules (SF = 2.5). Adding unstimulated human saliva to starch suspensions with native and limited swollen granules reduced friction and masked differences in friction coefficients among starch types. Both the salivary layer on the contact surfaces and the salivary proteins in the bulk phase played a role in determining lubrication properties. Graphical abstract: Unlabelled Image